PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN EDPUZZLE BERMUATAN TRI HITA KARANA PADA MATERI SIKLUS AIR MAPEL IPAS KELAS IV SEKOLAH DASAR - Made Juliartha Darma Putra; Komang Surya Adnyana; Gusti Ngurah Arya Yudaparmita (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Interactive Multimedia development supported by Edpuzzle and containing Tri Hita Karana values on the Water Cycle material for the fourth grade Elementary School Science subject is a Research & Development (R&D) development with the application of the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. However, the development in this study only reached the Development stage which was carried out at SD Negeri 3 Kampung Baru with data collection through observation, interviews, documentation, and questionnaires. The research subjects consisted of three experts in each aspect of media, language, and material, as well as three teachers and ten students. The results of the study show: (1) the process of designing Tri Hita Karana-based Edpuzzle-assisted Interactive Multimedia learning media begins with an analysis stage to identify learning problems and needs in the field, then continues with the design stage which includes preparing supporting facilities and creating media designs, (2) the validity of the media is in the